Ultrasound Assessment of Amniotic Fluid in Predicting Adverse Outcome in Prolonged Pregnancy - Sultana, P; Anwary, SA; Ahmed, ZU; Alfazzaman, M; Kulsum, U (Medicine Today, 2013)
DoI DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15006 Medicine Today 2012 Vol.24(2): 55-58